Residual Effect of Organic Manures on Rice Fallow Summerblackgram (Vigna Mungo L.) (Bangladesh Journal of Botany, 2023)
Field experiments were undertaken to ascertain the residual effect of organic manures on black gram crop in a rice-blackgram cropping sequence during summer seasons of 2017 and 2018 at Thoppur, Thirupparankundram, Madurai. Twelve treatments comprising various sources of nutrients (green manure, neem cake, enriched FYM, Panchagavya, tamarind seed powder) in a randomized block design with three replications laid out for rice were used to study the residual effect by growing blackgram in sequence. Basal incorporation of green manure @ 6.25 t/ha along with split application of vermicompost in four equal splits @ 4 t/ha as basal, at active tillering, panicle initiation and flowering stages + Panchagavya @ 3 per cent as foliar spray twice at active tillering and panicle initiation stages recorded the highest plant height, leaf area, dry matter production and grain yield. Increase in grain yield of 42.8 and 47.7 % was observed, respectively, during summer 2017 and summer 2018 over absolute control due to the residual effect of same treatment.Bangladesh J. Bot. 52(2): 235-241, 2023 (June)